Experiences of wake and light therapy in patients with depression: A qualitative study. (2nd November 2016) - Kragh, Mette; Møller, Dorthe Norden; Wihlborg, Camilla Schultz; Martiny, Klaus; Larsen, Erik Roj; Videbech, Poul; Lindhardt, Tove
Abstract: Wake therapy can reduce depressive symptoms within days, and response rates are high. To sustain the effect, it is often combined with light therapy. Few studies have focussed on factors related to patients′ adherence to the regime, and none has used qualitative methods to examine their experience of these combined interventions. Therefore, the aim of the present study was to illuminate patients' experiences with wake and light therapy and factors related to adherence. Thirteen inpatients with depression were included. They participated in an intervention consisting of three wake therapies during the first week, 30 min of daily light treatment for the entire 9 weeks, and ongoing psychoeducation regarding good sleep hygiene. Patients kept a diary, and individual semistructured interviews were conducted. Data were analysed using qualitative content analysis. The participants' overall experience with the treatment was positive. Some experienced a remarkable and rapid antidepressant effect, whereas others described more long‐term benefits (e.g. improved sleep and diurnal rhythm). Yet recovery was fragile, and patients were only cautiously optimistic. Social support was important for maintaining the motivation to stay awake and receive daily light therapy. Overall, participants found the treatment worthwhile and would recommend it to others with depression. The study revealed a lack of knowledge among participants about the connection between regular sleep patterns and depression. In conclusion, this study provides insight into patients' experiences, and knowledge that can contribute to guidelines for future adherence‐promoting organization of wake and light therapy.